2014
DOI: 10.1080/11745398.2014.906312
|View full text |Cite
|
Sign up to set email alerts
|

Orientalist obsessions: fabricating hyper-reality and performing hyper-femininity in Thailand's kathoey tourism

Abstract: servile and hypersexual transwomen have come to reinforce Thailand's reputation as an exotic and erotic playground. Despite their almost ubiquitious presence in tourist spaces, the theorization of transgender subjectivities from a localized Asian perspective tends to be glossed over in the literature on leisure and recreation, perhaps due to their complex position within a Western-centric, binary model of gender and sexuality. This paper attempts to fill this lacuna by mobilizing the concept of Orientalism and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…30 There are currently no studies on the prevalence of transgender persons in Thailand, although some studies have suggested a prevalence of 0.3–0.6%—roughly 10,000–660,000 people—of male-to-female transgender individuals in this country, but these figures may be significantly underestimated. 31 , 32 , 33 Transgender persons are becoming more visible in Thailand, with several healthcare facilities catering to their specific needs. Previous data from Thailand on increased gender dysphoria symptoms and poor quality of life are consistent with those from other studies and patients’ self-reports in other countries, although the Thai studies have not focused on gender confirmation surgery.…”
Section: Discussionmentioning
confidence: 99%
“…30 There are currently no studies on the prevalence of transgender persons in Thailand, although some studies have suggested a prevalence of 0.3–0.6%—roughly 10,000–660,000 people—of male-to-female transgender individuals in this country, but these figures may be significantly underestimated. 31 , 32 , 33 Transgender persons are becoming more visible in Thailand, with several healthcare facilities catering to their specific needs. Previous data from Thailand on increased gender dysphoria symptoms and poor quality of life are consistent with those from other studies and patients’ self-reports in other countries, although the Thai studies have not focused on gender confirmation surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies declared the use of interpretive or constructivist paradigm in passing, and only a few provided an in-depth discussion of the positionality of the researcher(s) (Coetzee et al, 2019;Gao & Kerstetter, 2016;Mura & Yuen, 2019;Pan, 2017;Wijesinghe, Mura & Culala, 2019b). Among the small proportion of qualitative studies that had moved beyond descriptive narratives to a more critical investigation of Asian tourism, postcolonial theory/lens was often cited (Mura & Sharif, 2015a;Mura & Yuen, 2019;Ranasinghe & Li, 2017;Tan, 2014;.…”
Section: Methodsmentioning
confidence: 99%
“…But it is in the discussion of “third order simulacra” that Baudrillard forges ground that has proven so productive for scholars of (auto‐)Orientalist tourist markets (e.g. Kasfir ; Steiner ; Tan ), as this category no longer refers to reproductions of the ostensibly “real,” overt or concealed, but a shift wherein representation, drawing on a cultural imaginary, itself produces realities. In Baudrillard's words, “the territory no longer precedes the map… [it is] the map that precedes the territory” (1994, 1).…”
Section: Orientalizing the Orientmentioning
confidence: 99%